Motivations for teaching and professional satisfaction: a study with teachers from the early years of Santa Maria, RS (Research, Society and Development, 2020)
In this article, we aim to analyze two aspects: motivation to teaching and professional satisfaction of 9 teachers from the initial years of elementary School of Santa Maria, RS.  The theoretical contribution is based on Gonçalves (1995), Imbernón (2009), Nussbaum (2015) among other authors. The research is of a qualitative approach and is centered on 14 narrative units collected in an interview, from the perspective of Bauer & Gaskell (2003). The analysis, referring to the motivations for teaching and professional satisfaction, constitutes a part of the master's thesis in the teaching of humanities and languages (MEHL), of the first author, attended by the Franciscan University (UNF). It was found that the motivation of the professional choice of most participants was due to intrinsic factors, associated with the influences of teachers who had and the stimulus of the family. Therefore, in the group studied, the lack of work option and the challenges that teaching presents were not decisive in the professional choice, it was also found that most had an intrinsic motivation for professional choice. In this choice, they exercised teachers ' influences and the family stimulus. In the group studied, the lack of work option and the challenges that teaching presents were not decisive in the professional choice.